MADRASAH PRINCIPAL POLICY MANAGEMENT: SYSTEMATIC LITERATURE REVIEW AND META ANALYSIS - Masdariah, Een; Tarihoran, Naf'an; Nugraha, Enung (Yayasan Education and Social Center, 2025)
Madrasa Principal policy management is a fundamental aspect in developing the quality of Islamic education which is currently facing complex challenges in the era of globalization and digital transformation. This research aims to identify effective policy management models for madrasah principals through a systematic literature review and meta-analysis approach. Using the PRISMA protocol, from the initial 35,276 articles, five high-quality articles were obtained for in-depth analysis. The research results show four main patterns in the policy management of madrasah principals: transition from top-down to collaborative approaches, integration of technology, emphasis on crisis management, and recognition of the emotional dimension. Meta-analysis shows that technology integration (effect size 0.76) and collaborative policy making (effect size 0.72) have the strongest influence on organizational effectiveness, while crisis management (0.48) and emotional leadership (0.53) show moderate influences. Overall, madrasah principal policy management had a significant positive impact (combined effect size 0.63) with moderate-high heterogeneity (I² = 68.7%). This research recommends developing an integrative policy management model that combines a collaborative approach with the use of technology, as well as expanding capacity development programs for madrasah heads that focus on crisis management skills and emotional intelligence.